Foot and Ankle - Schöffl, Volker; Simon, M. (Springer International Publishing, 2022)
Most injuries from falls in rock climbing result in pathologies of the feet and ankle. These are often standard foot injuries such as strains and sprains, ankle fractures and talus, or calcaneus fractures. Parallel to the late boom in indoor bouldering, we are seeing an increase in incidence of such accidents, since many falls onto the feet occur in bouldering. Additionally, there are chronic injuries to the feet caused by the very tight-fitting climbing shoes. The tight fit changes the biomechanics of the foot to deliver more strength from the feet onto the rock or wall. This results in chronic feet pain, subungual hematoma, callosities, bunions, deformities such as hallux valgus, and chronic osteoarthrotic conditions, for example, hallux rigidus. Also, in falls these tight shoes increase the risk of foot injuries, because they are not cushioned and do not stabilize the foot. Overall, climbing shoes should not be worn too tight, as this will cause chronic overstrain.
CRIS-Team Scopus Importer:2024-12-16